Implementing KWL (Know-Want to know-Learned) Strategy to Improve The 7th Graders’ Reading Achievement of SMP Negeri 12 Palembang - Putri, Ermalati; Anggaraini, Rini; Fiftinova, Fiftinova (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Based on the initial observation and information obtained from the English teacher of VII.10 Class at SMP Negeri 12 Palembang, the students’ reading ability is still low and needs improvement. This study is a type of classroom action research that aims to improve the reading achievement on descriptive texts by using the KWL (Know, Want to Know, Learned) strategy. The subjects of this research were 36 students of VII.10 Class at SMP Negeri 12 Palembang. The data were collected through observations, reading tests, and questionnaires. The quantitative data were analyzed using simple statistical methods, represented in percentages (%), while the qualitative data were analyzed descriptively. The results of this study indicated an improvement in both Cycle I and Cycle II. In the pre-action stage, out of thirty-six students, only fifteen students (42%) were able to meet the minimum criteria for mastery learning (Kriteria Ketuntasan Minimum/KKM), which was set at 75 by the school. In the first cycle, nineteen students (53%) achieved the KKM standard. Moreover, in Cycle II, thirty students (83%) reached the KKM, signifying that the reading test results in Cycle II met the targeted indicator of this classroom action research, which requires 75% of students to reach the KKM standard. Based on the results of the reading test, it can be concluded that the KWL Strategy effectively improves students’ reading achievement. Besides that, the data obtained from observations and questionnaires also showed positive results regarding the implementation of the KWL strategy in improving students’ reading skills. Several factors contribute to the successful implementation of the KWL strategy, including prior knowledge of the text, specific reading goals, and comprehension of acquired information.